Analisis Pendapatan Usahatani Tanaman Kelapa dalam (Cocos nucifera) Di Desa Lamahang Kecamatan Waplau Kabupaten Buru - La Jati Buton; Muhamad Chairul Basrun Umanailo; Adyla Mita Lestari (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2022)
The condition of coconut plantations is currently damaged due to very old age, especially in Lamahang Village, District. This situation causes the production of coconut plants to decrease greatly and the productivity of the land is very low. For this reason, it is necessary to do research on the analysis of coconut farming income in Lamahang Village. The objects to be studied are the farmers who own deep coconut, and to see the income of deep coconut farmers based on business patterns, the contribution of deep coconut farming to farmers' income, and the exchange rate of deep coconut farmers. For the sample taken 25%, from 100 heads of families the number of coconut farmers in Lamahang Village. The results showed that the average Farmer Terms of Trade (NTP) in coconut farming was 116.89. This means that in general it can be described that the level of welfare of coconut farmers in Lamahang Village, Waplau District, is still relatively prosperous.